ANALISIS PELAKSANAAN PENILAIAN AUTENTIK DALAM PEMBELAJARAN EKONOMI DI SMA NEGERI 1 PALEMBANG - Dewa Ayu Putu Setia Ari; Riswan Jaenudin; Dewi Koryati (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2019)
The study aimed to prove the Implementation of Authentic Assessment of Economic Learning in State Senior High School 1 Palembang reviewed from: (1) Implementation Authentic Assessment of Attitude Aspect, (2) Implementation Authentic Assessment of KnowledgeAspect, and 3) Implementation Authentic Assessment of Skills Aspect. This research is a descriptive research using a quantitative approaches. The subjects in this research are the Economic Teachers of the Palembang 1 State Senior High School class X and XI which had 3 teachers. Data collection techniques consist of observation, interviews and documentation. Data analysis techniques using Milles and Hubberman techniques with the presentation of inverted pyramid data are based on the highest to lowest indicators. The highest indicator is the Implementation of Authentic Learning in Economic Learning on Knowledge Aspects carried out through written test techniques, oral tests, and assignments with implementation categories (100%) which are very good Criteria. Implementation of Authentic Assessment of Economic Learning on Aspect Attitudes were carried out through observation techniques with implementation categories (90%) which are very good Criteria. Implementation of Authentic Learning in Economic Learning on Skills Aspects is carried out through performance and portfolio with implementation categories (88%) which are very good Criteria. Suggestions in this research were proposed on indicators of attitude and skill aspects.